IMPROVING THE STUDENTS’ MASTERY IN PRONOUNCING CONSONANTS /f/ AND /v/ (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2016)
This final project is concerned with the use of Cambridge Advanced Learner’s Dictionary toward the students’ pronunciation of consonants [f] and [v]. The objective of this study is to improve the students’ pronunciation by using Cambridge Advanced Learner’s Dictionary. This study used action research design. There were two cycles of action in this study. This research started with an initial pre-test and ended with a final post-test. In each cycle there were pre-test, treatment, and post-test. The tests were used to collect the quantitative data. Meanwhile, observation checklist and questionnaire were used to gather the qualitative data. Thirty one students of class VIII H of SMP N 22 Semarang were chosen as the subjects of this study. Based on the data analyses, there was a significant improvement of the students’ achievement after the implementation of Cambridge Advanced Learner’s Dictionary was given. This improvement was proved by the comparison between the result of Initial Pre-test and Final Post-test. This improvement was also supported by the results of observation checklists and questionnaire. Based on the observation checklists, the students’ attendance and engagement in Cycle 2 was better than their attendance and engagement in Cycle 1. Moreover, the result of questionnaire showed that the students gave positive perception towards the use of Cambridge Advanced Learner’s Dictionary. With regard to the above results, it can be concluded that the use of Cambridge Advanced Learner’s Dictionary successfully improves the students’ pronunciation of consonants [f] and [v]. Therefore, the use of Cambridge Advanced Learner’s Dictionary in the teaching pronunciation, especially pronunciation of English words containing consonants [f] and [v] is recommended.